Penggunaan Model Pembelajaran Predict Observe Explain Terhadap Keterampilan Proses Sains Siswa - Subagja, Adi; Jayadinata, Asep Kurnia; Iswara, Prana Dwija (Jurnal Pena Ilmiah, 2019)
Science process skills are important learning to be developed in elementary school. Predict observe explain (POE) is one of the alternative ways to improve science process skills on IPA learning in elementary school. The purpose of this research is to compare learning using POE with a conventional approach. This method of research uses quasi experiments with Nonequivalent control group design. The population of this research is all elementary school students in Cimanggung sub-class with research samples of SDN Parakanmuncang II class V-C as experimental class and V-A class as the control class. The results of this study indicate that. The results of research that has been done can be concluded that; There is a positive influence on learning using a POE model that shows the improvement of student science process skills in the experimental class, learning using POE models is better than a significant one than conventional learning In improving students ' science process skillsKeywords: Model predict observe explain, science process skills.